Determination of Theoretical Dispersion Curves on the Surface Phonon Polaritons in PTCDA - , Asih Melati dan Kamsul Abrahal ([Yogyakarta] : Fak. MIPA UGM, 2009)
Theoretical and computational studies of the polariton dispersion curves on the surface of the PTCDA organic material have been done, By applying the Modified Lorentz Oscillator Model (MLOM) of PTCDA (3,4,9,10 Perylene tetracarboxy/ic dianhydride/ CUHlJ06) has the dispersive dielectric function e (0) depending on the of wave frequency 0). The direction of Wave propagation is perpendicular to the easy axis. This study gives theoretical description of the PTCDA surface and bulk modes at f~equency range ~ =1.5 - 6 cm'l. 21rc The dispersion relation is obtained through Maxwell equation. Subtitution of electric (E) and magnetic ( H) fields into the wave differentialequation and application of boundary conditions will lead to the dispertion relations. The dynamics of internal or system parameters is included in the material permittivity. [t has been found that the surface polaritons only propagate in TM (Transverse Magnetic) mode and prove are reciprocal in the sense that the change of wave vector direction does not cause the change of frequency 0)( q) =0)(-q) . There is no surface polariton propagating in the TE (Transverse Electric) mode, but only bulk polaritons can propagate in this mode. The computed of ATR (Attenuated Total Reflection) spectra show that the surface polaritons can be detected optimally when the gap distance between the prism and the sample reaches an optimum value of O.8,um. Not Only variating the gap of distance between the prism, but also the effect of damp on the methods. [n this methods we are also trying to compare using of silicon prism and the other prism which different permittivity to reaches an optimum value of e p =II .56. The surface polariton modes are clearly verified in their reflectivity spectra, which are in agreement with the related dispersionrelations.